2021
DOI: 10.1097/hmr.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Promoting high-functioning mental health treatment teams in the context of low staffing ratios

Abstract: Background: Many previous studies of health care teamwork have taken place in clinical teams with high staffing ratios (i.e., high ratios of staff to patients). Purpose: The aim of this study was to identify clinicians' viewpoints of foundational resources necessary to support good team functioning in the context of low staffing ratios. Methodology: We used administrative data, validated with local mental health chiefs, to identify mental health teams that had achieved high team functioning despite low staffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Specifically, interview respondents noted that consistent leadership support for CCM-based BHIP teams, especially in the form of appropriate staffing and dedicated time for BHIP team meetings, was crucial to sustaining this model of care delivery. Other related work (Miller et al, 2022) has suggested that a "two-by-two" approach to team staffing, with each discipline having at least two representatives on the clinical team, may help protect against the negative impacts of staff turnover, as it allows for some level of continuity within the team even if one person leaves. In contrast, in the current project, in one case the presence of one influential nonsupportive leader (e.g., an Associate Chief of Staff) resulted in the dismantling of several years of BHIP-related process improvement work.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, interview respondents noted that consistent leadership support for CCM-based BHIP teams, especially in the form of appropriate staffing and dedicated time for BHIP team meetings, was crucial to sustaining this model of care delivery. Other related work (Miller et al, 2022) has suggested that a "two-by-two" approach to team staffing, with each discipline having at least two representatives on the clinical team, may help protect against the negative impacts of staff turnover, as it allows for some level of continuity within the team even if one person leaves. In contrast, in the current project, in one case the presence of one influential nonsupportive leader (e.g., an Associate Chief of Staff) resulted in the dismantling of several years of BHIP-related process improvement work.…”
Section: Discussionmentioning
confidence: 99%
“…We used a qualitative study design to examine the relational aspects of high-functioning clinician teams in the context of low staffing ratios. This paper builds on our work examining resources required to support team functioning in the context of low staffing ratio teams (Miller et al, 2021). This study was approved by the VA Boston Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…We used a two-step process to identify BHIP teams that achieved high-functioning despite low staffing ratios. First, teams were initially identified through administrative data from FY2017 (the last year with complete data at the time that we began identifying teams) including the VA All Employee Survey (AES), the VA Mental Health Provider Survey (MHPS), VA Corporate Data Warehouse (CDW), the VA Mental Health Management System (MHMS) and further detailed elsewhere (Miller et al, 2021; also see Supplemental File 1). Briefly, high-functioning BHIP teams were defined as those with high levels of self-reported job satisfaction, low burnout, and no plans or intentions to leave their current job (i.e., low turnover plans/intentions).…”
Section: Sampling and Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations